CAUSES OF CODE MIXING IN INTERACTION LEARNING INDONESIAN FOR CLASS VIII SMP NEGERI 1 AMBON - Novita Tabelessy; Sarleoky Umkeketony (Jurusan Pendidikan Bahasa dan Seni FKIP Universitas Pattimura, 2022)
Code mixing occurs when a speaken using a language predominantly supports a speech inserted wih other language elements. This is usually related to the characteristics of the speaker, such as social background, education level, religious taste, this is what experienced by class VIII students of SMP Negeri 1 Ambon. Factors causing code mixing in Indonesian language learning interactions are object of research. The type of research used is descriptive qualitative research, by using the method of observation, field notes and interviews. The data validity technique used by the researcher is the triangulation of sources and theories, and to analyze the factors causing code mixing in Indonesian language learning interactions, the researcher used three stages, namely data presentation, data description process, and verification or making conclusions. The research results found by the researcher were three factors that caused code mixing in the interaction of Indonesian language learning by class VIII students of SMP Negeri 1 Ambon, and the results prove that it is not only students who produce mixed codes in the learning process, but the teacher also produces mixed codes when communicating with students. The process of mixing codes produced by the teacher and students was apparently done unconsciously